Mengajarkan Kemampuan berpikir Tingkat Tinggi dengan Model Problem Based Learning Berbantuan Wondershare Quiz Creator - Nur Khoiri; Nur Ifanis Sa'adah; Joko Saefan (Jurnal Penelitian Pembelajaran Fisika, 2017)
The main purpose of this study is to investigate the effectiveness of Problem base learning assisted wondershare quiz creator on students’ high order thinking skills. The design of this study is true experimental which uses pre-test and post-test. This study is done in SMA Negeri 1 Sayung on September 25J uli − 8Agustus, 2017 which uses two classes as the sample and the sampling technique which the writer uses is Cluster Random technique. Based on the technique, the writer has gotten XI MIPA 1 as the experiment class and XI MIPA 2 as the control class. Moreover, the writer uses test and documentation as the techniques of data collection in this study. Based on the data analysis, the experiment class pre-test score is 32, 3 and the control class’s pre-test score is 31, 96. Meanwhile the post-test score of experiment class is 57, 3 and control class is 41, 6. Based on both classes pretest and posttest results, it shows that there is a significant different between the student’s self-employed and their study results in experiment class with the student’s self employed and their study results in control class. The hypothesis testing shows ttest = 3, 89 and ttable = 1, 667. This result shows that ttest > ttable (3, 89 > 1, 667) which means that H0 is declined. Therefore, it means that Problem based learning assisted wondershare quiz creator Method is able to cultivate students’ high order thinking skills